Going Beyond the Surface: A Case Report of Dressler’s Syndrome (Journal of Forensic Medicine & Toxicology, 2025)
Myocardial insufficiency is the most common cause of sudden death in young adults. Herein we discuss a case of Dressler’s  syndrome whose incidence is reported to be < 1-3% and is a cause that goes unreported. We report a case of young adult  of sudden death, whose cause of death on gross examination seemed to be that of myocardial insufficiency. Due to a high  index of suspicion after the history given by the relatives the cause of death gave us a deeper insight into his cause of  death. The relevance of this topic is to rely on the history and not ending the case on gross examination alone. A deeper  understanding of the cause will also increase the incidence of such cases which seem to be rare as they are not reported.
Keywords: Dressler’s Syndrome; Sudden Cardiac Death; Post-Myocardial Infarction; Pericarditis; Forensic Autopsy.